Efeitos cardiovasculares do (-)-ISOPULEGOL em animais normotensos e hipertensos - Santana, Izabel Rodrigues de (2024)
Systemic arterial hypertension (SAH) is a risk factor for the development of cardiovascular diseases (CVDs). Despite the availability of traditional pharmacological therapies, CVD morbidity and mortality remain a global challenge. This has spurred the investigation of the biological properties of plants, particularly terpenes, as a therapeutic approach due to their extensive biological effects on the cardiovascular system. (-)-Isopulegol ((-)-ISO) is a monoterpene with documented anti-inflammatory, antioxidant, and calcium channel- blocking properties. Therefore, the aim of this study was to evaluate the cardiovascular effects of (-)-ISO in normotensive and hypertensive animals. For this purpose, 76 normotensive and hypertensive male Wistar rats (hypertension induced by L-NAME 20 mg/kg for 7 days) were used (CEUAS: 2521170223/9546170223/1239150223). Mean arterial pressure (MAP) and heart rate (HR) were measured before and after intravenous administration of various doses of (-)-ISO (1, 5, 10, and 20 mg/kg) and pharmacological agents: atropine (ATR 2 mg/kg), indomethacin (INDO 5 mg/kg), hexamethonium (HEXA), and L-NAME (20 mg/kg) in normotensive rats. Hypertensive rats received oral (-)-ISO (200 mg/kg) and were evaluated over 48 hours. In vitro studies were conducted using the superior mesenteric artery of normotensive rats to assess vascular responsiveness to (-)-ISO (10-2-10- 6 M) and to elucidate the mechanisms of action associated with endothelium-independent pathways (K+ and Ca2+). The results demonstrated that (-)-ISO induced hypotensive and bradycardic responses in normotensive rats. Blockade with ATR or HEXA reduced bradycardia, suggesting the involvement of nicotinic receptors and indirect activation of muscarinic receptors in the bradycardic responses induced by (-)-ISO. However, blockade with L-NAME reduced only hypotension at the 10 mg/kg dose. Additionally, oral administration of (-)-ISO 200 mg/kg reduced hypertension in a sustained manner for 48 hours. In vitro studies highlighted that the hypotensive response may be associated with an endothelium-independent vasorelaxant effect, suggesting that (-)-ISO acts by inhibiting L- type voltage-sensitive calcium channels, interacting with IP3 receptors, and sensitizing the contractile machinery in vascular smooth muscle. These findings suggest that (-)-ISO is a promising candidate for future studies and pharmacological therapies.